Strategi Perencanaan dan Biaya Pemasaran yang Efektif bagi UMKM Mitra Binaan PT. Semen Indonesia Tbk - Erwin Saraswati (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play an important role in the economy, as they contribute to 57-60% of national GDP and employ 97% of all labors in the country. Besides raising capital, the main problem of MSMEs are marketing their products. Most MSME businessmen are merely product-oriented, not consumer-oriented and tend to focus only on fulfilling their families’ needs. So do the Fostered Partners of PT Semen Indonesia. After we conduct a training session, an FGD grouped by types of business, and knowledge sharing on web-based technology, MSMEs should be able to solve marketing-related problems and always budget marketing expenses.